Opinion 2425: Diplodocus Marsh, 1878 (Dinosauria, Sauropoda): Diplodocus longus Marsh, 1878 maintained as the type species - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has declined to use its plenary power to replace the type species of the sauropod dinosaur genus Diplodocus Marsh, 1878 with D. carnegii Hatcher, 1901.
Keywords: Nomenclature; taxonomy; Dinosauria; Sauropoda; Diplodocidae; Diplodocus; Diplodocus longus; Diplodocus carnegii; U.S.A.; Upper Jurassic Morrison Formation